(untitled) (Afrika und Übersee, 2022)
Naba, also known as Bilala, is a Nilo-Saharan (Sara-Bagirmi) language of Chad with about 410,000 speakers from three ethnic groups. This paper gives a basic description of the Naba phonological system, using segmental phonology and lexical phonology approaches. Topics covered include the phonemic inventory, syllable structure and phonotactic restrictions, the tone system and its interaction with other phonological processes, and the main lexical and post-lexical processes. A special focus is given to the important role of sonority hierarchy in Naba phonological structure and processes. This hierarchy groups affricates and non-sibilant fricatives with stops in a single obstruent category, while nasals, liquids, and approximants comprise the sonorant category. The distinction is key for syllable structure, phonotactic restrictions, tone sandhi, and a number of both lexical and post-lexical processes. It is proposed that the two sibilant fricatives /s/ and /z/ exist as a separate sonority level in between obstruent and sonorant, and evidence is given as to why they cannot be classed with either group.